HUBUNGAN MUTU PELAYANAN TERHADAP TINGKAT KEPUASANPASIEN PENGGUNA BPJS DI POLIKLINIK RUMAH SAKIT X TANGERANG TAHUN 2021 - Susilawati; Muryani Septi Wulandari (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction : Patient satisfaction can be created through good service by medical personnel in the health institution, thus if the service is not good, the patient who is dissatisfied will file a complaint with the hospital. While the quality of service Purpose: This study aims to determine the relationship between the quality of health services and the satisfaction level of BPJS users at the Polyclinic Hospital X Tangerang. Methods: The design of this study used a cross-sectional design or it could be called a cross-sectional study. Data collection was carried out by meansof a questionnaire. The number of respondents was 58 respondents. Results: The results obtained by the researcher were 39 respondents (67%) from 58 respondents who rated the quality of service as good and rated patient satisfaction with a satisfied value. In addition, there were also 19 respondents (33%) out of 58 respondents who rated the quality of service as adequate and patient satisfaction was lacking. Conclusion: Based on the above data, it can be concluded that there is a significant relationship between Service Quality and BPJS User Satisfaction Levels at the Polyclinic of RS X Tangerang in 2021 as evidenced by the value of Pearson Chi-Square = 0.000α. The results of the analysis used statistical tests using the Chi-Square correlation test, the value of Pearson Chi-Square = 0.000 <p (0.05), so Ho's conclusion was rejected, namely there was no relationship between service quality and BPJS patient satisfaction at the Polyclinic Hospital X Tangerang in 2021 Suggestion: In order for the quality of service to the level of patient satisfaction of BPJS users to be good.